(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Indian English literature has a long history of advancement and obviously that of Indian English Fiction. There are such a significant number of elements mindful in the commitment of the investigation of the fiction and spread of English language in India. Attempting hands on contemporary writing and then ruling over hearts of millions isn’t that simple as has been demonstrated by one of the conspicuous writers of the day – Chetan Bhagat. Not many creators have figured out how to connect with such a wide crowd as Chetan Bhagat. There is innovation of substance in his writings and when he composes people feel as though it is their story. He is a wonder that has influenced everyone, contacted everyone’s life. Chetan Bhagat’s Postmodernism writing offers India a blended pack of thoughts. It exemplifies reader well-disposed language with a style so novel and new. His novels are ―tugs at the emotions‖ instead of admonishes genuine abstract aspirations. In this article, we studied about the characters and the mistakes made by them in Chetan Bhagat Novels.